The Role of Akt in Chronic Liver Disease and Liver Regeneration - Morales-Ruiz, Manuel; Santel, Ansgar; Ribera, Jordi; Jiménez, Wladimiro (Seminars in Liver Disease, 2017)
The liver is continuously exposed to diverse insults, which may culminate in pathological processes causing liver disease. An effective therapeutic strategy for chronic liver disease should control the causal factors of the disease and stimulate functional liver regeneration. Preclinical studies have shown that interventions aimed at maintaining Akt activity in a dysfunctional liver meet most of the criteria. Although the central function of Akt is cell survival, other cellular aspects such as glucose uptake, glycogen synthesis, cell-cycle progression, and lipid metabolism have been shown to be prominent functions of Akt in the context of hepatic physiology. In this review, the authors describe the benefits of the Akt signaling pathway, emphasizing its importance in coordinating proper cellular growth and differentiation during liver regeneration, hepatic function, and liver disease.
Keywords: cirrhosis; nonalcoholic fatty liver disease; liver regeneration; viral hepatitis; Akt